Edible coatings for enhancing osmodehydration process of pears using glucose solution: a study on mass transfer kinetics and quality assessment - Campañone, Laura Analía; Soteras, Edgar; Rodriguez Racca, Anabel (Wiley, 2024)
The present study aimed to evaluate the combined application of edible coatings (alginate or pectin) and the osmotic dehydration process (glucose solution at 40 °Brix and 60 °Brix, solution temperatures of 20 and 40 °C, and process times of 1, 2, 4, 8, and 16 h) on mass transfer kinetics and physicochemical parameters (weight reduction (WR), water loss (WL), solids gain (SG), and optical and mechanical properties) of pear cubes. The best dehydration performance was observed in the coated samples treated at 60 °Brix-40 °C. At the end of this process, the coated samples showed higher values of WR (77.30% and 75.13%) and WL (77.39%; 74.38%) and lower values of SG (1.69% and 1.24%) than the uncoated samples (WR: 65.97%, WL: 68.38%, and SG: 4.12%). Additionally, optimal retention of optical and mechanical properties was achieved in the coated samples exposed to the 40 °Brix-40 °C condition.